Synthesis of towed underwater vehicle spatial motion automatic control system under uncertainty conditions - Blintsov, Volodymyr; Blintsov, Oleksandr; Sokolov, Volodymyr (Technology audit and production reserves, 2018)
The object of research is the towed underwater vehicle (TUV) spatial motion, operating as part of the towed underwater system (TUS). The TUV structure does not contain any propulsive devices; it is driven to the motion by the tugboat through the cable-tug. The task of controlling the TUV is provision of the desired dynamics of its translational motion. Manual control mode allows performing only short-term missions and does not exclude the occurrence of operator errors during control. To perform long underwater missions, it is necessary to use automated TUV. For the synthesis of automatic control system (ACS) controllers, the method of minimizing local functionals is used. It allows getting control laws without information about the structure and parameters of the mathematical model of the control object. To study the synthesized ACS, a simulation method using computer simulation is used. It allows assessing the ACS quality without significant financial costs necessary for the marine natural experiment. The ACS of TUV spatial motion is synthesized, it provides sufficient accuracy of control of the vertical and lateral coordinates of the TUV under uncertainty conditions. For its synthesis and operation, information about the structure and parameters of the mathematical model of the control object is not required. The control law, on the basis of which ACS controllers are synthesized, does not contain information on derivatives of a controlled variable. Therefore, the feedback loops of the synthesized ACS have a simple structure compared to the ACSs synthesized using the well-known methods that use the coordinates of the object’s phase space. The dynamics of the operation of the synthesized TUV spatial motion ACS was studied at various towing speeds. The duration of the transient processes from the moment the ACS exits the saturation zone to the moment the control error falls within the permissible range and the control accuracy are quite satisfactory. In comparison with the underwater vehicles known spatial motion ACSs, the synthesized ACS does not require a mathematical model of the control object for its synthesis and operation.